Fungal ball in urinary tract, a rare entity, which needs a specific approach - Praz, Valentin; Burruni, Rodolfo; Meid, Florian; Wisard, Marc; Jichlinski, Patrice; Tawadros, Thomas (Canadian Urological Association Journal, 2014)
A fungal mass in the urinary tract (fungus ball), mainly occurring in compromised patients, is a rare and dangerous complication of candiduria. We report 2 cases of fungus ball associated with hydronephrosis and sepsis. As reported in the literature, we treated the first patient by prompt relief of obstruction by nephrostomy and local and systemic antifungal agent. The second patient failed to respond to this treatment due to a distal ureteral stenosis and required open surgery with fungus ball removal and ureteral reimplantation. Despite a large success in urinary tract drainage with antifungal treatments, some cases need a modified approach due to anatomical modification.